Analyzing the use of adaptive learning in a flipped classroom for preclass learning. Issue 3 (5th March 2019) - Kaw, Autar; Clark, Renee; Delgado, Eleonora; Abate, Nicholas
Abstract: Preclass learning, an obstacle in the success of a flipped classroom, is addressed via placing lessons on an online adaptive platform. The lessons combine the power of video lectures, textbook content, simulations, and assessments while using personalized paths for each student. This article describes the development of the adaptive lessons for a course in Numerical Methods, and the interpretation of the analytic data collected via the adaptive lesson platform and student focus groups over a two‐semester period with 146 students. Analytical data includes student metrics, such as the lesson scores and the time spent and lesson metrics, such as the percentage of students who completed the lesson and the percentage of possible adaptive paths used by students. The focus groups were conducted for two different demographic groups—students who are "white males" (comprise the majority of students in public engineering schools in the USA) and "other than white males"—to compare their perspectives on adaptive learning. Students in the focus group of the "other than white male" pupils demonstrated more favorable and positive perspectives towards the adaptive learning compared with the "white males", although both groups identified benefits with the adaptive platform. Final examination scores were found to be correlated with the raw score of the adaptive lessons.